PENERAPAN SUB POKOK FUNGSI LINIER PADA MATEMATIKA EKONOMI TERHADAP ANALISIS BREAK EVEN POINT (ANALISIS IMPAS) - Susanti, Nawal Ika (Jurnal Ekonomi Syariah Darussalam, 2021)
The purpose of this study was to determine the responses and activities of students in studying the linear function material and its application to solve problems regarding BEP analysis. The method used is a quasi-experimental method using a one-shot case study research design. The results of this study indicate that the response of students in applying linear sub-functions in economic mathematics to BEP analysis has a good and positive response, namely 76.25%. And the dominant component is student participation which can be seen with the enthusiasm of students in practicing BEP analysis directly to economic actors around the IAIDA campus. Student activity in applying linear sub-functions in economic mathematics to the BEP analysis can be said to have increased seen from the average of each component during the observation which was 77.27%. This is because students can apply the concept of linear functions in completing the BEP analysis carried out by economic actors around campus by direct practice of economic actors.